Food production in the People's Republic of China - Tang, Anthony M.; Stone, Bruce (International Food Policy Research Institute, 1980)
Projections of Chinese agriculture to the year 2020 point to increased production and consumption of agricultural products, but major breakthroughs in productivity do not appear likely. Under conditions considered most plausible, rate of increase would exceed those of 1952-57 but would fall short of the Ten-Year Plan goals.